Functional evidence implicating FOXL2 in non-syndromic premature ovarian failure and in the regulation of the transcription factor OSR2. Issue 7 (7th May 2009) - Laissue, P; Lakhal, B; Benayoun, B A; Dipietromaria, A; Braham, R; Elghezal, H; Philibert, P; Saâd, A; Sultan, C; Fellous, M; Veitia, R A
Abstract : Background: FOXL2 encodes a forkhead transcription factor whose mutations are responsible for the blepharophimosis-ptosis-epicanthus inversus syndrome (BPES), involving craniofacial/palpebral abnormalities often associated with premature ovarian failure (POF). Results: We describe a FOXL2 variant (p.Gly187Asp) in a case of POF without BPES. The subcellular localisation of FOXL2-G187D was normal but its transactivation capacity tested on two reporter promoters, one of which should be relevant to the ovary, was significantly lower than that of normal FOXL2. However, FOXL2-G187D was able to activate strongly a reporter construct driven by the promoter of Osr2 ( odd-skipped related 2 transcription factor), which we have suggested to be a crucial target of FOXL2 in the craniofacial region. This is compatible with the absence of BPES in our patient. Conclusions: Our data provide evidence in favour of the implication of FOXL2 variants in non-syndromic POF and confirm the regulatory interaction between FOXL2 and OSR2 whose perturbation might contribute to the palpebral abnormalities observed in BPES patients.